Derrida vis-à-vis Lacan : interweaving deconstruction and psychoanalysis - Hurst, Andrea (Andrea Margaret) (Perspectives in continental philosophy., 2008)
This volume argues that the logical structure underpinning Lacanian psychoanalytic theory is a complex, paradoxical relationality that corresponds to Derrida's 'plural logic of the aporia'. Attempting to heal a long-standing divide between Lacanians and Derrideans, Hurst brings out a deep theoretical accord between the two thinkers.